The Influence of Social Media Communication and Health Service Quality on Patient Behavioral Intention: The Mediating Role of Patient Satisfaction and Patient Commitment Moderated by Corporate Image at Tritya Eye Clinic Surabaya - Triartomo, Anandio; Susanti, Nanis; Prastiwi, Estik Hari (International Journal of Economics (IJEC), 2025)
Tritya Eye Clinic, a developing eye clinic, must know what affects patient satisfaction. To understand patient preferences, four factors are key. They are: service quality, the role of social media, commitment, and clinic image. The problem is that patient satisfaction is still low. The roles of social media, consumer commitment, and the Tritya Eye Clinic's image are not optimal. This study aimed to assess the effect of social media and health service quality on patients' behavioral intentions. We examined satisfaction and commitment as mediators, and the company's image as a moderator, at Tritya Eye Clinic in Surabaya. This study uses a quantitative method. It got primary data by distributing questionnaires. the study population was all patients who had been treated at Tritya Eye Clinic Surabaya. We used non-probability purposive sampling to select 100 respondents. The data analysis method used descriptive analysis and SEM-PLS analysis. The results showed that social media and health service quality both had a positive, significant effect on users' intentions. This was through consumer satisfaction and commitment. and company image affects the link between commitment and consumer intentions at Tritya Eye Clinic, Surabaya.